VARIOUS COLOR OF JELAWAT (Leptobarbus hoeveni) FISH SAUSAGE - Suparmi Suparmi; Sumarto Sumarto; Desmelati Desmelati (Berkala Perikanan Terubuk, 2021)
The purpose of this research was to determine the chemical quality and consumer acceptance of the staple fish sausage fortified with natural dyes, namely carrot extract and red spinach extract. The research method used was experimental design (CRD), as the treatment was S0 (Jelawat fish meat). ), S1 (Jelawat fish meat added 20% red spinach extract), S2 (Jelawat fish meat added 20% carrot extract). From the results of the study of the preference test, it is known that the Jelawat  fish sausage with the addition of 20% carrot extract (S2) was preferred by consumers with a percentage (87.50%) with very like criteria and percentage (6.25%) like criteria. Organoleptic values are taste (8.0), aroma (8.5), appearance (8.3) and texture (8.6). The nutritional content of Jelawat sausage added with carrot extract was higher than the other treatments, with protein content (15.43%) moisture content (55.32%) fat content (2.43%) ash content (6.19%) and carbohydrate content (20.63%). The characteristics of the sausage are thick and brass colored, fishy aroma and carrot aroma is more dominant, fish taste is slightly sweet and carrot-like, while the texture is dense and elastic.